2013
DOI: 10.5267/j.msl.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of default probability in banking industry using CAMELS index: A case study of Iranian banks

Abstract: This study examines the relationship between CAMELS index and default probability among 20 Iranian banks. The proposed study gathers the necessary information from their financial statements over the period [2005][2006][2007][2008][2009][2010][2011]. The study uses logistic regression along with Pearson correlation analysis to consider the relationship between default probability and six independent variables including capital adequacy, asset quality, management quality, earning quality, liquidity quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…ratio (Loans to Total Assets), and third ratio (Loans to Deposits), which are considered the best predictors of bank distress. Valahzaghard and Bahrami (2013) found a meaningful relationship between default probability and management quality, earning quality and liquidity quality. Samad (2011) found significant differences in capital adequacy (capital to average total assets, capital to risk weighted assets, equity capital to assets, and Tier 1 capital to risk-weighted assets) between unhealthy and healthy banks.…”
Section: Related Literaturementioning
confidence: 86%
See 3 more Smart Citations
“…ratio (Loans to Total Assets), and third ratio (Loans to Deposits), which are considered the best predictors of bank distress. Valahzaghard and Bahrami (2013) found a meaningful relationship between default probability and management quality, earning quality and liquidity quality. Samad (2011) found significant differences in capital adequacy (capital to average total assets, capital to risk weighted assets, equity capital to assets, and Tier 1 capital to risk-weighted assets) between unhealthy and healthy banks.…”
Section: Related Literaturementioning
confidence: 86%
“…Since then, logistic regression (Al-Saleh & Al-Kandari, 2012;Valahzaghard & Bahrami, 2013;Zaghdoudi, 2013), genetic algorithms (Martin, Gayathri, Saranya, Gayathri, & Venkatesan, 2011), multivariate discriminant analysis (Canbas, Cabuk, & Kilic, 2005;Demyanyk & Hasan, 2009), multivariate regression analysis (Meyer & Pifer, 1970), artificial neural networks (Ravi & Pramodh, 2008), and fuzzy models (Tung, Quek, & Cheng, 2004;Yildiz & Akkoc, 2010) have served as general models for predicting bankruptcies. ratio (Loans to Total Assets), and third ratio (Loans to Deposits), which are considered the best predictors of bank distress.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…For this last pillar, nancial institutions should maintain e ective processes for disclosing information and displaying transparency to the market. e studies found in the literature on predicting financial distress are based on samples of financial institutions from the European Union (Betz, Oprica, Peltonen, & Sarlin, 2014), Russia (Peresetsky, Karminsky, & Golovan, 2011), North America (Cleary & Hebb, 2016;Lane, Looney, & Wansley, 1986), Iran (Valahzaghard & Bahrami, 2013), and Malaysia (Wanke, Azad, & Barros, 2016), as well as cross-country samples (Liu, 2015).…”
Section: Introductionmentioning
confidence: 99%